New record of Pelecitus sp (Nematoda, Onchocercidae) as a parasite of Athene cunicularia (Strigiformes, Strigidae) in southeastern Brazil - Silva, Tarcsio Macedo [UNESP] (2014)
The aim of this study was to report the burrowing owl Athene cunicularia as a new host for the filarid nematode Pelecitus sp. in southeastern Brazil for the first time, as well as reporting the occurrence of this nematode species in the body cavity, near the cervical air sac and lung region. This study contributes towards knowledge of parasitism in Brazilian wild birds and an anatomical region of the host as an infection site for Pelecitus sp.